1998
DOI: 10.1021/jp981960z
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of the Chirality of Organic Molecules by Scanning Tunneling Microscopy

Abstract: Scanning tunneling microscopy (STM) has been used to study the chiral molecules (R)/(S)-2-bromohexadecanoic acid at the liquid/solid interface. When adsorbed onto the basal plane of graphite, these molecules segregate on the surface into domains of pure R or S enantiomers. The atomic resolution obtained in the STM images of these species allows a direct assignment of the chirality of individual molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
153
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(165 citation statements)
references
References 15 publications
(38 reference statements)
10
153
2
Order By: Relevance
“…[12][13][14][15] In some cases, indications of spontaneous chiral segregation of racemic films have been reported. [16][17][18][19] When the substrate atomic order is affected, even chiral restructuring may occur. 20 Finally, chirality may be expressed at the supramolecular level in discrete molecular assemblies at surfaces which are stabilized by noncovalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] In some cases, indications of spontaneous chiral segregation of racemic films have been reported. [16][17][18][19] When the substrate atomic order is affected, even chiral restructuring may occur. 20 Finally, chirality may be expressed at the supramolecular level in discrete molecular assemblies at surfaces which are stabilized by noncovalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning tunnelling microscopy (STM) imaging at submolecular resolution has offered a great deal of information on the local structure, chiral organization, separation and recognition of both intrinsically chiral and prochiral molecules on surfaces [14][15][16][17][18][19] . Interestingly, experiments have revealed that the enantiomer units may be intermediate chiral assemblies of smaller achiral molecules 20 , and may even form on mirror symmetric (non-chiral) substrates such as high-symmetry noble metal surfaces 21 .…”
mentioning
confidence: 99%
“…The occurrence of chiral preference may be an important step in the heterogeneous catalytic conversion of prochiral reagents into one of possible optical isomers. Such enantioselectivity is usually induced by adsorbing chiral molecules onto catalytically active surfaces [4]. This is why a characterization of chiral centers in adsorbed molecules is desirable.…”
mentioning
confidence: 99%